POLA BANTUAN HUKUM DALAM MENCEGAH TERJADINYA TINDAK PIDANA KEKERASAN SEKSUAL - Nasution, Rasina Padeni (Universitas Muhammadiyah Ponorogo, 2024)
The legal aid model is an effort to ensure that every citizen, especially those who are less fortunate, has access to justice. This study aims to describe the implementation of the legal aid models employed by legal aid institutions to prevent sexual violence crimes in the city of Medan. The research method used is empirical juridical research, which examines the law based on facts in society and considers the function of the law. The analysis technique employed is descriptive analysis. The results of the study show that the implementation of the structural legal aid model (BHS) by LBH Medan and the structural gender legal aid model (BHGS) by LBH APIK are effective models in providing legal protection by expanding access to justice for victims. These models focus on recovery and the enhancement of premium services based on an approach to justice that not only aims to resolve cases through legal channels but also strives to change unjust social structures due to power relations, aiming towards more equal social relations and a gender perspective. The conclusion of this study indicates that the implementation of BHS by LBH Medan and BHGS by LBH APIK plays a significant role in both preventive and repressive efforts to prevent and address sexual violence in the city of Medan. These models also serve as solutions in synergizing stakeholders in advocating for sexual violence cases in the city of Medan.